2021
DOI: 10.3390/toxins13090603
|View full text |Cite
|
Sign up to set email alerts
|

Apamin Enhances Neurite Outgrowth and Regeneration after Laceration Injury in Cortical Neurons

Abstract: Apamin is a minor component of bee venom and is a polypeptide with 18 amino acid residues. Although apamin is considered a neurotoxic compound that blocks the potassium channel, its neuroprotective effects on neurons have been recently reported. However, there is little information about the underlying mechanism and very little is known regarding the toxicological characterization of other compounds in bee venom. Here, cultured mature cortical neurons were treated with bee venom components, including apamin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…This study builds on previous work in which BV and its major components (bvPLA2, melittin, and apamin) demonstrated a neuroprotective effect on neurodegenerative diseases such as Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis, as well as on neurite outgrowth and regeneration after cortical neuron injury [ 28 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This study builds on previous work in which BV and its major components (bvPLA2, melittin, and apamin) demonstrated a neuroprotective effect on neurodegenerative diseases such as Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis, as well as on neurite outgrowth and regeneration after cortical neuron injury [ 28 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 54%
“…These two major components of BV showed a minor effect on re-innervation in contrast to the whole bee venom. This can be explained by the involvement of other BV molecules in the regeneration process such as apamin that accelerate neurite outgrowth and axon regeneration after a laceration injury in vitro [ 28 ]. It was found that the whole BV and melittin are efficient in the treatment of chemotherapy-induced neuropathy [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it gains indirect support by the notion that mellitin, another related bee venom, enhances wound healing [ 34 , 37 ]. In addition, apamin has been shown to enhance the regeneration of injured cortical neurons in vitro [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above results showed that MEL could be a candidate agent for neurodegenerative disorders ( Cong Duc and Lee, 2021 ). Apamin enhanced neurite outgrowth and axon regeneration after laceration injury, and increased the expression of BDNF, nerve growth factor (NGF) and regeneration-related genes in mature cortical neurons ( Kim H. et al, 2021 ). Apamin inhibited LPS-induced neuroinflammatory responses in BV2 and rat primary microglial cells.…”
Section: Effects On Neurological Disordersmentioning
confidence: 99%